Performance analysis of neuro linguistic programming techniques using confusion matrix - Kumar, Arun; Panda, Supriya P. (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
During numerous qualitative surveys, swish patterns and visual kinesthetic dissociation (V/KD) were employed to examine attitudes and past occurrences. Neuro-linguistic programming (NLP) workshops in both hypnotic and non-hypnotic experimental sessions were held for forty days. Results demonstrated that negative sentiments and various emotional factors were significantly higher in 10-days’ workshop sessions as compared to 40 days’ sessions. Following the qualitative sentiments recollection, NLP workshops with various activities in the fear and stress indexing segment were increased in length. The NLP procedure was followed by the decreased negative emotional intensity in both groups; also, the results have been improved when using swish patterns and V/KD techniques. The performance analysis shows the results of improving emotional and sentimental factors in various NLP workshops. The workshops ranged in length from five to forty days. The specifications for workshops were selected based on the human mind's pre-determined conditions. The performance factors of two significant NLP techniques used in NLP workshops were compared and both techniques' performance factors were found to be adequate in terms of modifying behavior patterns. Using the confusion matrix, the overall accuracy percentage between V/KD and swish patterns is calculated, and an increase from 0.65 to 0.83 in the stressed parameters is shown.